Osteopontin is essential for IL‐1β production and apoptosis in peri‐implantitis. (15th February 2018) - Che, Chengye; Liu, Jie; Yang, Jianjun; Ma, Lei; Bai, Na; Zhang, Qian
Abstract: Background and Purpose: Peri‐implantitis is caused by a cascade of host and microbial factors leading to an oral inflammatory disease. The inflammation proliferates into supporting tissues surrounding implants and may finally lead to a complete loss of osseointegration. Being a phosphorylated glycoprotein secreted by immunocompetent cells, osteopontin (OPN) is involved in the differentiation of odontoblast‐like cells during pulpal healing following tooth transplantation and the secretion of type I collagen in reparative dentin. But the production and function of OPN in peri‐implantitis has not been thoroughly evaluated. Materials and Methods: Peri‐implant crevicular fluid (PICF) was collected from 28 healthy implants patients and 28 peri‐implantitis patients to determine the expression of OPN in response to the inflammation of peri‐implantitis by Western‐blot, Enzyme‐linked immunosorbent assay (ELISA), and immunofluorescence staining. THP‐1 macrophages infected by Porphyromonas gingivalis were chosen to reveal the production and function of OPN in peri‐implantitis by immunofluorescence staining, quantitative polymerase chain reaction (RT‐PCR), and Western‐blot. Results: Results showed that OPN increased in most PICF of peri‐implantitis patients and in THP‐1 macrophages stimulated with P. gingivalis . The expression of OPN in response to P. gingivalis decreased at mRNA and protein levels when exposed to either the lectin‐type oxidized LDL receptor 1 (LOX‐1) neutralizing antibody or inhibitor pretreatment in THP‐1 macrophages. P. gingivalis induces OPN through the Erk1/2 MAPK dependent pathway. OPN neutralization decreased interleukin 1 beta (IL‐1β) expression on P. gingivalis infection, and the lower IL‐1β mRNA and protein levels were rescued by human osteopontin recombinant protein (rhOPN) in THP‐1 macrophages. RhOPN suppressed P. gingivalis induced apoptosis of the mitochondrial pathway in THP‐1 macrophage. Conclusions: Overall, the results of this study provide insight into the essential roles of OPN for IL‐1β production and apoptosis in peri‐implantitis, as supported by the evidence from the study of patient's PICF and cell culture experiments.